ANALYSIS OF LAND COVER CHANGE IN THE MANGROVE FOREST IN AIR TELANG PROTECTED FOREST AREA, BANYUASIN REGENCY, INDONESIA: (Analisis Perubahan Tutupan Lahan di Hutan Mangrove di Kawasan Hutan Lindung Air Telang Kabupaten Banyuasin, Indonesia) - Budi Utomo; Helfa Septinar (Majalah Ilmiah Globe, 2022)
Mangrove has an ecological and climate control function, but mangrove forests continue to decrease so that they threaten wetland ecosystem. This study aims to determine the spatial change of mangrove forest land cover in the Air Telang Protected Forest (ATPF) Area of Banyuasin Regency. The materials used in this study are Landsat 8 image in 2013, 2015 and 2018. Identified by mangrove forests using normalized difference vegetation index . Analysis of changes in mangrove land using multitemporal data in 2013, 20 di15 and 2018. The accuracy of the classification of mangrove forest in the ATPF of Banyuasin Regency was accuracy overall certification on Landsat imagery 8 in 2013 of 93%, in 2015 of 93% and in 2018 of 94%. Mangrove forest in the air telang protection forest area of Banyuasin Regency has a trend of decreasing the extent of both the core zone and the utilization zone. Causes of Mangrove Areas loss are population, economic activity and natural factors. Changes in the extent of mangrove forest cover in the air telang protection forest area of Banyuasin Regency from 2013 to 2018 there was a decrease in the area of mangrove forests covering an area of 5,021 hectares